Key performance indicators (KPIs) comparison of food chain reactor and conventional oxidation ditch technology in industrial waste treatment - Temmy Wikaningrum; Rijal Hakiki (Journal of Environmental Engineering and Waste Management, 2020)
The oxidation process as the activated sludge (AS) system has been implemented widely in urban and industrial wastewater treatment. Oxidation ditch can be categorized as an advanced aeration activated sludge. Integrated Fix-Film Activated Sludge (IFAS) process has been already developed for decades that was a reasonable approach for technology to upgrade the activated sludge wastewater treatment plant (WWTP). IFAS processes are a combination of biofilm reactors and activated sludge processes, biofilm is introducing and retaining as the carrier media for microorganism growth. Both IFAS and AS processes can achieve similar percent removal of COD and ammonia. Current WWTP’s development was food chain reactor (FCR) which mainly IFAS process of engineered media that combining with natural plants with the plant roots submerging into the reactors. The references review and secondary data of the application in  Jababeka’s WWTP-2 for both AS and FCR system showed that FCR is needless parameters to be controlled. In both AS and FCR have KPIs of flow rate (m3/day), F/M ratio, energy consumption  (kWh/m3 wastewater), Oxygen supply (kgO2 / m3 wastewater in each reactor, % removal of COD, BOD, TSS, NH3, TKN, NO2, and heavy metals, and pH, Dissolved Oxygen, microorganism performance in the reactor. Different from AS, the FCR system is not required to control the parameters of sludge retention time (SRT), recirculated activated sludge (RAS), sludge volume index (SVI), and mixed liquor suspended solids (MLSS)of activated sludge.